The predictive factor for conjunctival melanoma recurrence - Agus Supartoto; Melita Suwan Djaja; Didik Setyo Heriyanto; Endang Soetristi; Datu Respatika; Muhammad Bayu Sasongko (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2019)
Conjunctival melanoma potentially deadly tumor. While many cases of conjunctival melanoma appeared to be a recurrence, there is no valid data about parameters to predict the recurrence of this tumor. This study intended to evaluate whether histopathologic features can be used as a predictor for recurrence in conjunctival melanoma. This was a retrospective study, involving patients with conjunctival melanoma by the year 2013-1017 in Dr. Sardjito General Hospital and Dr. Yap Eye Hospital, Yogyakarta. Patient’s characteristic was determined by age, sex, laterality, tumor size, tumor location, histopathological dominancy, MMC application, recurrence, and metastases. Sixteen cases were found: male (62.5%) and female (37.5%). Age from 5-79 years, mean was 56.19 years. Tumor location was in bulbar in 11 patients (68.7%), palpebral in 5 patients (31.3%).There was significant association between metastasis and the tumor recurrence (OR 13.0; 95% CI 1.9-85.4; p = 0.007). A favorable trend of association was also found between location and the recurrence of melanoma (OR 15.0; 95% CI 0.9-228.8; p = 0.06). In summary, our study showed that the patients that developing distant metastasis were at a greater risk for tumor recurrence.